Ekstraksi DNA total dari sumber jaringan hewan (Ikan Kerapu) menggunakan metode kit for animal tissue - Yanti Ariyanti; Sister Sianturi (Journal of Science and Applicative Technology, 2019)
DNA extraction is a series of processes to separate DNA from other cell components. Extraction is the most crucial early stage in molecular research. There are two methods in DNA extraction: traditional organic extraction and non-organic adoption extraction method. Traditional organic extraction method are used by many laboratories to obtain amount of high-yield DNA. However, in recent years it has been a tendency to adopt non-organic commercial protocols, known as extraction kit. This method was relatively faster, low times-consuming and avoid the toxicity due to phenol use. This study aims to determine the steps of DNA extraction to obtain total DNA from muscle tissue of fish grouper using Extraction Kit for Animal Tissue. The Kit extraction method has an advantages that is the processing time is shorter, simple, non-toxic and high-purity DNA yields. A total of 4 tissue samples from grouper muscle were successfully extracted using an Extraction Kit that was indicated by the visualization of the band on qualitative DNA analysis in 1% agarose gel. Keywords: DNA extraction, extraction kit, high-yield DNA, molecular method